Evaluation of the mandibular canal in stereolithographic biomedical prototypes (Research, Society and Development, 2024)
Objective: The purpose of this research was to evaluate through an experimental study the positioning accuracy of the mandibular canal of sterolithographic prototypes, also comparing them with the dry human jaws which served as the basis for their manufacture. Material and methods: 10 human jaws (20 mandibular canals) were submitted to computed tomography examination and reproduced in transparent stereolithographic biomodels with evidence of the mandibular canals, so that linear measurements between previously determined could be performed and compared. For data analysis was used the t test of paired samples, and p values < 0.05 were considered statistically significant. Results: The results obtained revealed that there is a statistically significant difference of approximately 10.21% between the measurements obtained in dry mandibles and biomodels. Finally, the similarity and variability of intra and inter-examiner probabilities were evaluated, and a strong agreement was found in both cases, demonstrating the reproducibility of the method used. Conclusion: More studies are needed before using the mandibular canal of stereolithographic prototypes as a parameter for clinical use.